Analisis Faktor-Faktor Yang Memengaruhi Perilaku Pencarian Pelayanan Kesehatan Pada Program JKN Di Indonesia - Risma Pertiwi; Aghniya Choirunnisa; Zahra Septina; Riswandy Wasir; Novita Dwi Istanti (Jurnal Medika Nusantara, 2023)
The National Health Insurance (JKN) program aims to improve access to health services and achieve universal health coverage for all Indonesians. However, there are still several issues related to access and quality of health services that have not been resolved, one of which is health service seeking behavior, which is one of the important principles of the JKN program. The method used in this research is a literature study by collecting and processing previous research data with a range of 2018-2022, consisting of 5 national articles and 1 international article. The search process was carried out through the Central Bureau of Statistics database, Google Scholar, and PubMed. The results of this study are the factors that influence people's behavior in seeking health services in the JKN program in Indonesia are divided into 3 main factors, namely predisposing factors, enabling factors, and need factors. In addition, there are other factors such as sociocultural beliefs, perceptions of disease and its causality, cost, and accessibility and availability of health services, especially in rural areas.